Comparative assessment of liquid product from hydrothermal treatment of lignosulfonate in batch and nozzle reactors for aromatic compounds recovery. (May 2023) - Sobek, Szymon; Tran, Quang Khanh; Junga, Robert; Sajdak, Marcin; Werle, Sebastian
Abstract: Lignosulfonate is one of the main by-products of the pulping process, with enormous potential for application as an alternative source of aromatic and bioactive compounds, especially in a closed-loop Circular Economy Concept. The lignin-derived bioactive compounds have attracted enormous interest in the scientific community due to their positive effects on human health. In the present paper, hydrothermal treatment technologies of the 10 wt% and 20 wt% lignosulfonate solutions i.e., slow HTL in batch reactor and fast HTL in continuous-flow (CF) reactor, are compared, and discussed, to assess their potential for obtaining bioactive and aromatic compounds. The hydrothermal liquefaction (HTL) in the two reactors was carried out at 275 °C at a pressure of 21.4 MPa, a 1:3 feed-to-water ratio. GC-MS and LC-MS-QTOF analyses were used to determine the chemical composition of the liquid products. According to the chromatogram integrated peak areas (PA), the fast HTL of the lignosulfonate produced the most isoeugenol (35.8–49.2%), eugenol (10.4–16.9%), and homovanillyl alcohol (13.8–18.4%). Slow HTL product, on the other hand, was rich in guiacol (62%) and apocynin (19.7%). LC-MS analysis of the product showed a similar composition to the liquid product in terms of heaviest compounds. Observed m/z values in the chromatograms indicated a presence of the compounds with masses between 121.159 and 934.021 u, possible configurations of the polycyclic phenolic compounds are presented. Highlights: Fast HTL of the LS produced isoeugenol, eugenol, and homovanillyl alcohol. Batch slow HTL product, on the other hand, was rich in guiacol and apocynin. Slow LS processing favor reactions of isoeugenol and vanillin to guaiacol. Observed m/z values indicated compounds with masses between 121.159 and 934.021 u.